2022
DOI: 10.3390/su142416710
|View full text |Cite
|
Sign up to set email alerts
|

Geotechnical Characteristics of Fine-Grained Soils Stabilized with Fly Ash, a Review

Abstract: Fly ash is a waste material obtained from burning of coal in thermal power plants. Coal consumption is still very high and is expected to remain above 38% globally. Therefore, large volumes of fly ash are produced every year that need to be managed as waste. Improper disposal of fly ash can lead to surface water and ground water pollution and adversely affect human health and environment. The use of fly ash as an agent to stabilize soil has recently become popular in geotechnical engineering due to its many be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 91 publications
1
11
0
Order By: Relevance
“…The increase in CBR is due to the presence of angular particles in the EDW, which mobilizes the angle of internal friction, resulting in an increase in strength. Similar behavior was observed by several researchers [15,17,20,31,33].…”
Section: California Bearing Ratio (Cbr) Testssupporting
confidence: 90%
See 1 more Smart Citation
“…The increase in CBR is due to the presence of angular particles in the EDW, which mobilizes the angle of internal friction, resulting in an increase in strength. Similar behavior was observed by several researchers [15,17,20,31,33].…”
Section: California Bearing Ratio (Cbr) Testssupporting
confidence: 90%
“…Moreover, the addition of EDW and AEFA reduced the clay size fraction of the soils due to flocculation of clay particles through cementation. Therefore, EDW and AEFA treatment made the soil more granular [20,[31][32][33]. Additionally, decreasing PI increased the workability of the soils.…”
Section: Atterberg Limit Testsmentioning
confidence: 99%
“…Improving geotechnical properties of clayey soils with fly ash has been studied for a while in geotechnical engineering. The recent studies on stabilizing silt and clay soils by fly ash were gathered in a paper as a review and it was shown that fly ash can be used as a substitute material to improve the mechanical properties of fine-grained soils [5]. However, studies on the improvement of sand soils with fly ash have been limited; Kaniraj and Havanagi [6] added fly ash and cement to sand and silt soils and found that cement had a greater effect than fly ash.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, feasible ground treatment must be resorted to before constructing any structures on them. Many researchers have conducted extensive studies to produce simple, sustainable, economical, environmentally friendly, and effective methods for ground improvement (Anburuvel, 2023;Ly & El-Sayegh, 2023;Turan et al, 2022;Zada et al, 2023;Ziar et al, 2023). Since then an extensive range of ground improvement techniques have been developed to improve poor ground conditions.…”
Section: Introductionmentioning
confidence: 99%